P164 Cyclophosphamide for the treatment of refractory chronic hypersensitivity pneumonitis. (December 2018) - Hastings, RA; Saunders, P; Hogben, C; Mackintosh, JA; Patel, S; Chua, F; Renzoni, EA; Kokosi, M; Kouranos, V; Wells, AU; George, PM; Maher, TM; et al.
Abstract : Introduction: Intravenous cyclophosphamide at a dose of 600 mg/m 2 monthly for 6 months is an established treatment for various immune modulated interstitial lung diseases (ILDs). This practice has been extended to rapidly progressive chronic hypersensitivity pneumonitis (CHP), however, little is known about the therapeutic efficacy in this disease. Methods: All patients receiving intravenous cyclophosphamide between 2007 and 2017 at the Royal Brompton Hospital were identified using pharmacy records. Those with a clinical diagnosis of CHP underwent MDT review to confirm the diagnosis. Clinical data, demographics and lung function at time of first treatment and 12 months pre- and post was captured. Results: One hundred and twenty patients with CHP prescribed IV Cyclophosphamide were identified. Three received a lung transplant and 9 had no follow up data available and were therefore excluded. At time of treatment the remaining 108 patients had a mean age of 61.4±11 years, were predominantly female (67%), non-smokers (72%) with severe disease (DLco 33%±10.6% predicted; FVC 57.5%±18% predicted). Only 64 patients (59%) received all 6 planned infusions. Nine patients died before completing therapy, 4 continued to decline and therapy was discontinued or switched and 32 (30%) stopped because of side effects. Infective episodes were the commonest cited reason for discontinuation (53% (17/32)), with others including haematuria, nausea and vomiting and deranged LFTs. In the cohort who completed therapy the average decline in FVC and DLCO in the preceding 12 months was −8±18% and −18.3±18% respectively and post cyclophosphamide this decreased to −1.2±15% and −3.8±17% (p=0.02). Only 16 patients who received all 6 doses experienced a decline of >10% in FVC in the following 12 months and the mean survival was 3.17 years. Conclusions: Patients with severe CHP who tolerate a full course of IV cyclophosphamide demonstrated a stabilization in decline in lung function. While the marked improvements seen with therapy in CTD-ILD are not observed the arrest of a rapid decline is an important intervention in this devastating disease. However, just over half of the patients who commenced therapy tolerated the full course and further work is needed to identify those likely to respond.